Peran Moderasi Fasilitas Belajar dan Relevansi Prediktif Model terhadap Prestasi Belajar Siswa SMP SATU ATAP di Kabupaten Belu - Yohanes Masan Bria; Shine Pintor Siolemba Patiro; Taufani Chusnul Kurniatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effects of teacher competence, teacher performance, and parental involvement on students’ academic achievement, as well as to investigate the moderating role of learning facilities. This research employed a quantitative approach using a survey method, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that teacher competence and parental involvement have a positive and significant effect on students’ academic achievement. In contrast, teacher performance does not have a significant direct effect on academic achievement. The moderation analysis reveals that learning facilities weaken the relationship between teacher competence and academic achievement, while strengthening the relationship between teacher performance and academic achievement. However, learning facilities do not moderate the relationship between parental involvement and academic achievement. These findings support the relevance of Social Exchange Theory and Epstein’s Parental Involvement Framework in explaining factors influencing students’ academic achievement. This study provides important implications for educational stakeholders in designing policies related to teacher quality improvement, the provision of learning facilities, and the strengthening of sustainable school–family partnerships.